N1-methylnicotinamide promotes age-related cochlear damage via the overexpression of SIRT1 - Miwa, Toru; Tarui, Akihito; Kouga, Teppei; Asai, Yasunori; Ogita, Hideaki; Fujikawa, Taro; Hakuba, Nobuhiro (Frontiers in Cellular Neuroscience, 2025)
Age-related hearing loss (ARHL) is a complex condition with genetic, aging, and environmental influences. Sirtuins, particularly SIRT1, are NAD-dependent protein deacetylases critical to aging and stress responses. SIRT1 is modulated by nicotinamide N-methyltransferase (NNMT) and its product, N1-methylnicotinamide (MNAM), which influence ARHL progression. While SIRT1 is protective under certain conditions, its overexpression may paradoxically exacerbate hearing loss. This study examines MNAM supplementation’s impact on SIRT1 expression and ARHL in low-fat diet (LFD)-fed B6 and CBA mice. Mice were divided into LFD and LFD + MNAM groups and evaluated for auditory function, cochlear morphology, metabolic profiles, and SIRT1 expression at 3, 6, and 12 months of age. MNAM supplementation accelerated ARHL in both strains, with B6 mice showing more pronounced and earlier disease progression. Auditory brainstem response (ABR) thresholds were significantly elevated, and distortion-product otoacoustic emissions (DPOAE) indicated outer hair cell dysfunction. Cochlear histology revealed reduced hair cell and spiral ganglion cell counts, as well as decreased Na+/K+-ATPase α1 expression and endocochlear potential. MNAM increased SIRT1 protein levels in the cochlea without altering Sirt1 mRNA, suggesting post-transcriptional regulation. Metabolomic analysis revealed disrupted mitochondrial and oxidative pathways, including fatty acid oxidation and gluconeogenesis. Tricarboxylic acid (TCA) cycle dysregulation was evident, particularly in B6 mice, with elevated pyruvate, fumarate, and lactate levels. Despite similar metabolic trends in CBA mice, their slower aging profiles mitigated ARHL progression. These results suggest that while moderate SIRT1 expression protects against ARHL, overexpression disrupts metabolic homeostasis, accelerating cochlear aging and dysfunction. The dual role of SIRT1 emphasizes the need for precise modulation of its expression for effective therapeutic interventions. Future research should explore mechanisms underlying SIRT1-induced cochlear damage and strategies to maintain balanced SIRT1 expression. This study highlights MNAM’s detrimental effects on ARHL, underscoring its significance for developing targeted approaches to delay ARHL onset and preserve auditory function.